LEFORT’S COLPOCLIESIS IN ELDERLY WOMEN HAVING PELVIC ORGAN PROLAPSE AND MEDICAL CORMORBIDITIES - Khatoon, Uzma; Abbasi, Aziz un Nisa (Journal of Ayub Medical College Abbottabad, 2015)
Lefort’s colpocliesis is surgery done in patients having pelvic organ prolapse associated with medical co-morbidities. Added to this it is done in elderly patients no more interested in marital relations. This procedure is not commonly done in our setup and there are few case reports in our region. We have very few successful case of this procedure. Here we are presenting a report of successful repair. This elderly lady presented to us with chief complaints of 3rd degree prolapse. She was diagnosed as a cardiac patient after proper investigation, so she was unfit for general anaesthesia and major surgery. Ultimately she was operated upon lefort’s procedure. On her first follow-up visit she was having healthy wound and good satisfaction.